THE CRIMINAL DEAD AGAINST THE PERPETRATORS OF THE CRIME OF NARCOTICS - Hamid, Suryana (Journal of Humanity, 2016)
Research conducted in Pinrang Regency District Court. The expected goal of researchis to know the elements of the crime of narcotics number 09/Pid. B/2015/PN.Prg.Data obtained by direct interviews with the resource person, and search thearchives/documents as well as reading literature related to the problems discussed.Data analysis was done using qualitative analysis.The research results showed that: (1) the elements of a criminal offence are containedin the Court ruling number 09/Pid. B/2015/PN. Prg has been proven by the defendantfulfills the elements in section 114 subsection (2) of the Act of the Republic ofIndonesia Number 35 in 2009. (2) the form of consideration given by the defendantbefore giving an award is to pay attention to the aspect of incriminating the accusedand defendants as well as relieve the aspect social values contained in its communityenvironment with reference to the existing legislation.